High rate and large intercentre variability in retreatment of retinopathy of prematurity in infants born <24 gestational weeks. Issue 1 (21st April 2021) - Lundgren, Pia; Jacobson, Lena; Hård, Anna-Lena; Al-Hawasi, Abbas; Larsson, Eva; Gränse, Lotta; Saric, Marie; Sunnqvist, Birgitta; Tornqvist, Kristina; Wallin, Agneta; Holmstrom, Gerd E; Smith, Lois LE; et al.
Abstract : Objective: Prematurity is a major risk factor for retinopathy of prematurity (ROP). We aimed to elucidate ROP prevalence, treatment and retreatment in infants born before 24 gestational age (GA) weeks in a Swedish cohort. Methods and analysis: Infants with completed ROP screening, born at <24 GA weeks, 2007–2018 in Sweden were included. Data of GA, birth weight (BW), sex, neonatal morbidities, maximal ROP stage, aggressive posterior ROP (APROP), ROP treatments, treatment modality and treatment centre were retrieved. Results: In total, 399 infants, with a mean GA of 23.2 weeks (range 21.9–23.9) and a mean BW of 567 g (range 340–874), were included. ROP was detected in 365 (91.5%) infants, 173 (43.4%) were treated for ROP and 68 of 173 (39.3%) were treated more than once. As the first treatment, 142 (82.0%) received laser and 29 (16.1%) received intravitreal injection of antivascular endothelial growth factor (anti-VEGF). Retreatment was performed after first laser in 46 of 142 (32.4%) and in 20 of 29 (69.0%) after first anti-VEGF treatment. Retreatment rate was not associated with GA, BW or sex but with APROP, treatment method (anti-VEGF) and treatment centre where the laser was performed (p<0.001). Twenty eyes progressed to retinal detachment, and two infants developed unilateral endophthalmitis after anti-VEGF treatment. Conclusion: Infants, born at <24 weeks' GA, had high rates of treatment-warranting ROP and retreatments. Treatment centre highly influenced the retreatment rate after laser indicating that laser treatment could be improved in some settings.